The Budget Impact of Oral Nutritional Supplements for Disease Related Malnutrition in Elderly in the Community Setting - Freyer, Karen; Nuijten, Mark J.; Schols, Jos M. (Frontiers in Pharmacology, 2012)
A health economic analysis was performed to assess the economic impact on the national health care budget of using Oral Nutritional Supplements (ONS), being a food for special medical purposes (FSMP) also known as medical nutrition, for the treatment of disease-related malnutrition (DRM) in the community in the Netherlands. An economic model was developed to calculate the budget impact of using ONS in community dwelling elderly (> 65 years) with DRM in the Netherlands. The model reflects the costs of DRM and the cost reductions resulting from improvement in DRM due to treatment with ONS. Using ONS for the treatment of DRM in community dwelling elderly, leads to a total annual cost savings of € 13 million (18.9% savings), when all eligible patients are treated. The additional costs of ONS (€ 57 million) are more than balanced by a reduction of other health care costs, e.g. re-/hospitalization (€ 70 million). Sensitivity analyses were performed on all parameters, including duration of treatment with ONS and the prevalence of DRM. This budget impact analysis shows that the use of ONS for treatment of DRM in elderly patients in the community may lead to cost savings in the Netherlands.